Theoretical and experimental study of a micro jet engine start-up behaviour - Montazeri-Gh, Morteza; Fashandi, Seyed Alireza Miran; Jafari, Soheil (Faculty of Mechanical Engineering in Slavonski Brod, Faculty of Electrical Engineering in Osijek, Faculty of Civil Engineering in Osijek, 2018)
Proper functioning of the start-up process in a micro jet engine is of great importance. This is due to the fact that the combustion chamber of such engine is so small and therefore, there is little time for fuel and air mixture to be present in the chamber. Hence, failed starts or repetitive attempts by the electric starter are very likely due to non-formation of the initial combustion. Also, the performance of the turbine start-up, impressively affects the limited life time of the micro jet engine. In this paper, an experimental study on the injection of compressed air during the start-up of a micro jet engine to improve its performance has been conducted. For this purpose, test components’ layout and a monitoring system are designed. The allowable pressure of the air injection has been calculated using both the engine dynamic model and experimental tests. The simulation results have also been compared and validated with the experimental test results. Finally, several tests were conducted to study the injection process of the compressed air form which, several results have been deduced including the reduction of maximum exhaust gas temperature (EGT) during the start-up, reduction of the start-up time interval and service lifetime enhancement. The method proposed in this paper is applicable on any micro jet engine with the similar structural form and starting process.
Keywords: Dynamic modelling; Experimental test; Micro jet engine; Start-up